Flavor characterization of microfermented cacao beans - Mangaser, Ma. Bernardita Roman; Gatchalian, Miaflora M.
A cabinet microfermentary for the small scale (2.5 kg.) fermentation of cacao beans was developed. The heat developed naturally during large-scale fermentation was simulated in the microfermentary through the use of electric light bulbs. Temperature and pH measurements of the fermenting cacao beans in the microfermentary were done to determine if the cabinet microfermentation proceeded in the same way as the normal fermentation. Two batches of cacao beans were fermented in the cabinet microfermentary for 2, 4, 6, and 8 days. Physical and chemical tests were conducted on the microfermented and sun-dried cacao samples. ANOVA results showed significant differences between the unfermented sample and the microfermented samples in terms of the compounds believed to be responsible for flavor development. Duncan's multiple Range Test showed significantly higher reducing sugar contents, sugar indices, soluble nitrogen contents and nitrogen indices for microfermented samples compared to those unfermented. Significantly lower tannin and anthocyanin contents for microfermented samples was also found. There was no clear relation established between microfermentation and fat content. The volatiles of roasted, microfermented bean, F4, F6, and F8 gave gas chromatograms similar to that of the Ghana commercial sample. The unfermented beans on the other hand, had a different gas chromatographic pattern and a much lower concentration of volatile compounds. Chocolate floavor was noted on the microfermented cacao samples both by the local chocolate manufacturer and the taste panel employed in this work for sensory evaluation. Microfermentation also significantly decreases the bitterness and astringency of cacao samples were more acidic than the unfermented sample. The results obtained indicate that the cabinet microferemtary developed brought about fermentation changes in the beans. These changes were similar to those obtained for a commercial sample of Ghana beans. Flavor evaluation however differed. Future work calls for a better comparison of fermentation changes between experimental and commercially fermented beans, to verify the applicability of the microfermentary as a research tool or as a village-level equipment for cacao fermentation.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Keywords: Cocoa; Fermentation